2021
DOI: 10.1371/journal.pone.0244394
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers and construction of a microRNA‑mRNA regulatory network for clear cell renal cell carcinoma using integrated bioinformatics analysis

Abstract: With the recent research development, the importance of microRNAs (miRNAs) in renal clear cell carcinoma (CCRCC) has become widely known. The purpose of this study is to screen out the potential biomarkers of renal clear cell carcinoma (CCRCC) by microarray analysis. The miRNA chip (GSE16441) and mRNA chip (GSE66270) related to CCRCC were downloaded from the Gene Expression Omnibus (GEO) database. After data filtering and pretreating, R platform and a series of analysis tools (funrich3.1.3, string, Cytoscape_ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…After a series of analyses for these 23 miRNAs, miR-532-3p was identified as the most potential miRNA of PLAUR, which was negatively associated with PLAUR expression; it was overexpressed and predicted a bad outcome in KIRC. Moreover, Han et al suggested that miR-532-3p inhibited the malignant progression of KIRC by downregulating the expression of ETS1, an oncogene associated with unfavorable prognosis in KIRC (44). Subsequently, 121 upstream potential lncRNAs of the miR-532-3p-PLAUR axis were discovered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After a series of analyses for these 23 miRNAs, miR-532-3p was identified as the most potential miRNA of PLAUR, which was negatively associated with PLAUR expression; it was overexpressed and predicted a bad outcome in KIRC. Moreover, Han et al suggested that miR-532-3p inhibited the malignant progression of KIRC by downregulating the expression of ETS1, an oncogene associated with unfavorable prognosis in KIRC (44). Subsequently, 121 upstream potential lncRNAs of the miR-532-3p-PLAUR axis were discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Han et al. suggested that miR-532-3p inhibited the malignant progression of KIRC by downregulating the expression of ETS1, an oncogene associated with unfavorable prognosis in KIRC ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microarray technology can be reliable and useful for identifying novel targets for clinical diagnostic and therapeutic approaches. This technology can be used in pancreatic cancer and renal clear cell carcinoma for diagnosis and effective therapy [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although hsa-mir-142 and hsa-mir-3676 have not been implicated in renal cancer in the literature, our final candidate, hsa-mir-133b, has been associated with renal cancer through the JAK2/STAT3 pathway [47]. It has also been identified as a biomarker in other studies [48].…”
Section: Discussionmentioning
confidence: 99%
“…CHL1 is an ATP-dependent DNA helicase that promotes genomic stability through DNA replication, DNA repair, and ribosomal RNA synthesis [51]. CHL1 was found to be a prognostic marker for renal cancer by multiple sources [50, 52], suggesting that under-expression can lead to lower survival rates in renal cancer patients. HAPLN1 is a protein that binds hyaluronic acid with proteoglycan monomers [51].…”
Section: Discussionmentioning
confidence: 99%